2017
DOI: 10.1093/jac/dkx022
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of MDR Mycobacterium tuberculosis isolates to unconventional drugs compared with their reported pharmacokinetic/pharmacodynamic parameters

Abstract: Most drugs demonstrated efficacy against M. tuberculosis . When these MICs are compared with the published pharmacokinetic/pharmacodynamic profiles of the respective drugs in humans, trimethoprim/sulfamethoxazole, meropenem/clavulanate, linezolid, clofazimine and nitazoxanide appear promising and warrant further clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Overall, the results of the studies identified in this review, which used a variety of experimental methods to test clinical and laboratory strains of M. tuberculosis for susceptibility to carbapenems, are consistent. Carbapenems are more active against M. tuberculosis if used in combination with clavulanate, a BLaC inhibitor (8,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). In line with these in vitro studies, the addition of clavulanate improved the survival rate in mice (33).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Overall, the results of the studies identified in this review, which used a variety of experimental methods to test clinical and laboratory strains of M. tuberculosis for susceptibility to carbapenems, are consistent. Carbapenems are more active against M. tuberculosis if used in combination with clavulanate, a BLaC inhibitor (8,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). In line with these in vitro studies, the addition of clavulanate improved the survival rate in mice (33).…”
Section: Discussionmentioning
confidence: 83%
“…Multiple studies reported that meropenem in the presence of clavulanate is active in vitro against clinical and laboratory strains H37Rv and H37Ra of M. tuberculosis, showing MICs of Յ1 mg/liter. In vitro studies reporting susceptibility to meropenem of M. tuberculosis reference strains and clinical isolates showed MICs of between 1 and 32 mg/liter (8,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Meropenem in combination with clavulanic acid was shown to have MICs of between 0.063 and 32 mg/liter (31-33, 36, 41).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NTZ has been reported to inhibit the growth of diverse strains of MTb cultured in cell-free media (Cavanaugh et al., 2017, de Carvalho et al., 2009, de Carvalho et al., 2011, Harausz et al., 2016, Odingo et al., 2017, Piccaro et al., 2013, Shigyo et al., 2013). In one study using an H37Rv-luciferase reporter MTb strain, NTZ inhibited MTb replication in THP-1 cells when measured at 24, 48, and 72 h after infection (Lam et al., 2012).…”
Section: Resultsmentioning
confidence: 99%